A Comparative Analysis of Students Writing Before and After Using AI Tools - Tazkiyah Marwah Arina; Otong Setiawan Djuharie (Indo Publishing, 2026)
The use of artificial intelligence (AI) tools in academic settings has increased significantly, including in assisting students to write in English. However, few studies have directly compared the quality of students' writing before and after using such tools. This study aims to analyze the comparison of fourth-semester students' writing in the English Literature Program at UIN Sunan Gunung Djati Bandung before and after using AI tools (such as ChatGPT or automatic translators). The method used is descriptive quantitative with a comparative approach. Data were collected from 9 students who were asked to rewrite an Indonesian text into English without AI assistance, and then rewrite the same text with AI assistance. The results showed that writing with AI assistance achieved higher average scores (70–95) compared to writing without AI assistance (12–85). The most common errors in writing without AI included grammar issues (tenses, prepositions, subject-verb agreement) and incomplete sentences. In contrast, writing with AI assistance tended to be more structured and aligned with standard English grammar rules. This study concludes that AI tools are effective in helping students improve their grammar and writing completeness, but supervision is still needed to prevent students from becoming fully dependent on AI.